2007
DOI: 10.2337/db06-1454
|View full text |Cite|
|
Sign up to set email alerts
|

Zinc, Not Insulin, Regulates the Rat α-Cell Response to Hypoglycemia In Vivo

Abstract: The intraislet insulin hypothesis proposes that the decrement in ␤-cell insulin secretion during hypoglycemia provides an activation signal for ␣-cells to release glucagon. A more recent hypothesis proposes that zinc atoms suppress glucagon secretion via their ability to open ␣-cell ATPsensitive K ؉ channels. Since insulin binds zinc, and zinc is cosecreted with insulin, we tested whether decreased zinc delivery to the ␣-cell activates glucagon secretion. In streptozotocin-induced diabetic Wistar rats, we obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 23 publications
2
88
3
Order By: Relevance
“…Impaired pathways with respect to the inhibitory effect of hyperglycemia on glucagon secretion, referred to as a-cell resistance, have been identified in studies of a-cell lines (Xu et al 2006). Interestingly, a switch-off signal from zinc atoms, whether bound to insulin or not, also seems to be involved in the initiation of glucagon release from the a-cell, as could be shown in streptozotocin-induced diabetic Wistar rats (Zhou et al 2007). The removal of somatostatinmediated inhibition of glucagon secretion via pancreatic d-cells by sympathetic activation may further contribute to inadequate glucagon secretion (Hauge-Evans et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Impaired pathways with respect to the inhibitory effect of hyperglycemia on glucagon secretion, referred to as a-cell resistance, have been identified in studies of a-cell lines (Xu et al 2006). Interestingly, a switch-off signal from zinc atoms, whether bound to insulin or not, also seems to be involved in the initiation of glucagon release from the a-cell, as could be shown in streptozotocin-induced diabetic Wistar rats (Zhou et al 2007). The removal of somatostatinmediated inhibition of glucagon secretion via pancreatic d-cells by sympathetic activation may further contribute to inadequate glucagon secretion (Hauge-Evans et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Zinc also has a paracrine effect on neighbouring cells, notably on α cells where it can inhibit glucagon secretion [88]. Thus, the cessation of zinc secretion under hypoglycaemic conditions could act as a trigger for glucagon secretion from α cells at proximity [92,93].…”
Section: Effects Of Secreted Zn 2+mentioning
confidence: 99%
“…On one hand, it has been found that Zn 2C activates K ATP channels and decreases glucagon release in isolated rat a-cells (Ishihara et al 2003, Franklin et al 2005. Zn 2C seems to be the switchoff signal to initiate glucagon secretion during hypoglycaemia in streptozotocin-induced diabetic rats (Zhou et al 2007a). However, these results contrast with the absence of effects on mouse a-cells (Ravier & Rutter 2005).…”
Section: Regulation Of Glucagon Secretion By Fatty Acids and Amino Acidsmentioning
confidence: 99%